Kineto-Elastodynamic Analysis of Watt's Mechanism Using ANSYS. (2016) - Mehta, Manish
Abstract: Kineto-elastodynamic analysis deals with the study of kinematic and dynamic analysis of a mechanism by considering the elasticity and distribution of mass in link. In present paper finite element method for kineto-elastodynamic analysis of high speed planar four bar mechanism has been presented. Based on the work done by previous researchers, well known displacement finite element method has been used to develop the mass and stiffness properties of an elastic linkage. The mechanism is modeled as beam element and its equation of motion is expressed in a matrix form. An accurate and efficient method to determine the strain in different link of Watt's mechanism using ANSYS has been presented, considering flexibility of a link at high speed. The results obtained using ANSYS have been validated by comparing them with experimental results available in literature for four bar mechanism, and are found to be is close agreement with experimental results. The same methodology has been further applied for analysis of Watt's mechanism.